Description of a new species, Caryanda Stal, 1878 (Acrididae, Orthoptera) from China. (3rd April 2017) - Hu, Zhou; Guan, De-Long; Mao, Ben-Yong
Abstract: A new species, Caryanda xinpingensis Maosp. nov., was described and illustrated. The specimens of its type are deposited in the Biological Science Museum, Dali University (BMDU), Yunnan Province, China. The complete mitochondrial genome of the species was sequenced and annotated. The obtained genome contains 15, 445 bp with an A + T content of 75.3%. A phylogenetic tree constructed with all 13 mitochondrial protein-coding genes showed the phylogenetic placement of C. xinpingensis Maosp. nov. near Pseudoxya diminuta, as the sister group to a clade containing the genus Oxya, both belonging to Oxyinae subfamily as expected. http://zoobank.org/urn:lsid:zoobank.org:pub:1F54EC2B-2187-442A-BB84-A467FA15187D